Recent progress on power scaling and single-frequency operation of 1.7-μm thulium-doped fiber lasers. (February 2023) - Zhang, Junxiang; Fu, Shijie; Sheng, Quan; Zhang, Lu; Shi, Wei; Yao, Jianquan
Highlights: The principle and recent efforts on efficient short-wavelength operation of Tm 3+ -doped fiber lasers at 1.7 μm have been introduced. Key factors and main obstructions towards achieving high-power 1.7 μm Tm 3+ -doped fiber lasers have been analyzed. Recently developed techniques of linewidth narrowing to achieve single-frequency 1.7 μm laser operation have been summarized and discussed. Abstract: Efficient, narrow-linewidth Tm-doped fiber lasers operating in the 1.7 μm wavelength regime are of significant importance for a wide range of applications. To achieve high-power 1.7-μm laser emission directly from Tm-doped fiber, signal reabsorption losses and gain competition with 1.8–1.9 μm emission band should be significantly addressed. In this paper, we reviewed the recent progress on 1.7-μm Tm-doped fiber lasers, where novel technical routes toward laser efficiency improvement and single-frequency laser operation have been proposed and demonstrated. Details on the developed techniques and the corresponding laser performance are overviewed while potential development direction is also discussed to provide a reference to develop high-power and single-frequency fiber laser sources.